Novel Role of p-Toluenesulfonamide in the Preparation of 4,5-Diaminocyclopent-2-enones - Liu, Jinqian; Yu, Jianjun; Zhu, Mengyun; Li, Jun; Zheng, Xingzhou; Wang, Limin (Synthesis, 2013)
A new and efficient protocol for the preparation of 4,5-diaminocyclopent-2-enones via the reaction of N-sulfonylimine with secondary amines, with p-toluenesulfonamide acting as a leaving group, is presented. In addition, p-toluenesulfonamide worked well as a catalyst even with a catalytic amount for the reaction of 2-furaldehyde and secondary amines to afford the corresponding products in higher yields.
Keywords: TsNH2; p-toluenesulfonamide; leaving group; catalyst; secondary amines; 4,5-diaminocyclopent-2-enones